(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
According to CERI of OE CD professional development should be in the focus of teachers’ in—service training within the educational policy of the member states. Nowadays, when the widening of the school’s function in socialization goes hand in hand with the structural expansion of teacher roles, responding to these expectations teachers can gain knowledge in the area of interdisciplinary pedagogy if they are offered in—service training fulfilling professional and inter-sector expectations. Our research has mapped the supply characteristics of the accredited Hungarian in-service training system, and compared it with real teacher needs and demands. We claim that both on the demand and on the supply sides the training content aimed at developing teachers’ skills and competences and at background knowledge promoting the education and treatment of children with a wider interpretation of special needs which area is rather loosely attached to subject teaching is underrepresented.